Enhanced aerobic sludge granulation in a Sequencing Batch Reactor (SBR) by applying mycelial pellets. (20th November 2020) - Geng, Mingyue; Ma, Fang; Guo, Haijuan; Su, Delin
Abstract: The positive roles of carriers in aerobic granulation have been widely acknowledged. To our current knowledge, most researches have focused on using inorganic or inert carriers to enhance aerobic granulation, and there is a lack of investigations on applying biomass carriers in aerobic granular sludge (AGS) system. In this study, the feasibility of a novel strategy by applying mycelial pellets (MPs) to enhance aerobic granulation was evaluated. Two lab-scale sequencing batch reactors, namely R1 and R2, were operated for 80 days. R1 was operated with mixture of MPs and activated sludge, and R2 (control reactor) had no MPs. Lab-scale SBR operation showed the addition of MPs significantly accelerated aerobic granulation and enhanced the biomass retention in R1. Morphology characterization revealed that mature granules in R1 had a larger size (3.1 mm) than those in R2 (2.3 mm). Besides, a unique structure with channels was observed in granules of R1. In terms of pollutant removal performance, R1 presented slightly higher values of COD (92.69%), nitrogen (70.45%), and phosphorus (74.66%) removal efficiencies than R2 (90.46%, 64.51%, 70.23%). Further investigations revealed the extracellular polymeric substances (EPS) production in R1 was enhanced during granulation, especially extracellular protein (PN), indicating that PN had a significant contribution to the granulation process under the novel strategy. High throughput sequencing analysis showed that more EPS producers and bacteria involved in biological nutrient removal were successfully enriched in R1. Overall, applying mycelial pellets is an effective and environmentally-friendly strategy for enhancing aerobic granulation. Graphical abstract: Image 1 Highlights: An effective and environmentally-friendly aerobic granulation strategy was proposed and investigated. Mycelial pellets were applied as biomass carriers to enhance aerobic granulation. The granulation process developed from filaments dominated granules into bacteria dominated granules under the strategy. Granules formed with mycelial pellets addition exhibited a unique structure with channels. The addition of mycelial pellets enhanced extracellular protein production in aerobic granular sludge system.